Analysis Of Differences In Share Prices Before And In Covid-19 Pandemic Era(Case Studies In The Sub-Sector Of Telecommunications, Hotel And Tourism, Health, Bumn Finance, And Transportation Listed On The Indonesia Stock Exchange) - et. al., Vanny Christianti, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the differences of share prices in the telecommunications, hotel and tourism, health, finance and transportation sub-sectors listed on the Indonesia Stock Exchange before and in the Covid-19 pandemic era. An analysis of stock price movements is carried out by investors to reduce investment risk. This aim is to minimize the possibility of losses from investment activities, especially in the midst of the Covid-19 pandemic that occurred at the beginning of March 2020. The existence of this outbreak caused the Composite Stock Price Index (ISHG) to weaken due to the application of Large-Scale Social Restrictions (PSBB) or social distancing by the government. However, stock trading activities are still valid and carried out. The research method used is descriptive and verification methods with a quantitative approach, using the research sample consisted of 28 companies. The results showed that descriptively the average stock price development in the telecommunications, hotel and tourism, health, finance, and transportation sub-sectors experienced fluctuations which tended to decline as a result of the Covid-19 pandemic. Meanwhile, based on verification study show that there is a significant difference between the share price at telecommunication, hotel and tourism, health, finance, and transportation sub-sector before and in pandemic era.